An Empirically Derived Definition of Metabolically Healthy Obesity Based on Risk of Cardiovascular and Total Mortality - Zembic, Anika; Eckel, Nathalie; Stefan, Norbert; Baudry, Julia; Schulze, Matthias B (JAMA Network Open, 2021)
IMPORTANCE: People classified by a priori definitions as having metabolically healthy obesity have frequently been found to be at increased risk of mortality, compared with individuals with metabolically healthy normal weight, suggesting these definitions may be insufficient. OBJECTIVES: To systematically derive a new definition of metabolic health (MH) and investigate its association with cardiovascular disease (CVD) mortality and total mortality. DESIGN, SETTING, AND PARTICIPANTS: In a cohort study using data from the third National Health and Nutrition Examination Survey (NHANES-III), a representative survey using complex multistage probability sampling, anthropometric factors, biomarkers, and blood pressure (BP) associated with total and CVD mortality among participants with obesity were identified with Cox proportional hazards regression. Area under the receiver operating characteristic was calculated to identify predictive factors for mortality to be used to define MH, cutoff levels were determined by the Youden index, and the findings were validated through comparison with the independent UK Biobank cohort, a population-based prospective study. All nonpregnant participants in the databases aged 18 to 75 years with no history of CVD, body mass index greater than or equal to 18.5, and who fasted 6 or more hours before examination in NHANES-III were included; participants in the UK Biobank cohort who did not have blood measurements were excluded. The study was conducted from 2015 to 2020. EXPOSURES: Body mass index and MH were defined by the new definition and compared with 3 a priori definitions. MAIN OUTCOMES AND MEASURES: Cardiovascular disease mortality and total mortality. RESULTS: Within the NHANES-III (n = 12 341) cohort, mean (SD) age was 41.6 (29.2) years, 50.7% were women, and mean follow-up was 14.5 (2.7) years. Within the UK Biobank (n = 374 079) cohort, mean (SD) age was 56.2 (8.1) years, 55.1% were women, and mean follow-up was 7.8 (1.0) years. Use of blood pressure (BP)-lowering medication (hazard ratio [HR] for CVD mortality, 2.41; 95% CI, 1.50-3.87 and total mortality, 2.05; 95% CI, 1.47-2.84), diabetes, and several continuous factors were associated with mortality. Of all significant continuous factors, the combination of systolic BP and waist-to-hip ratio showed the highest area under the receiver operating characteristic (CVD mortality: 0.775; 95% CI, 0.770-0.781; total mortality: 0.696; 95% CI, 0.694-0.699). Thus, MH was defined as systolic BP less than 130 mm Hg, no BP-lowering medication, waist-to-hip ratio less than 0.95 for women and less than 1.03 for men, and no self-reported (ie, prevalent) diabetes. In both cohorts, metabolically healthy obesity was not associated with CVD and total mortality compared with metabolically healthy normal weight. For NHANES-III, the hazard ratio was 0.68 (95% CI, 0.30-1.54) for CVD mortality and 1.03 (95% CI, 0.70-1.51) for total mortality. For UK Biobank, the hazard ratio was 1.17 (95% CI, 0.81-1.69) for CVD mortality and 0.98 (95% CI, 0.87-1.10) for total mortality. Regardless of body mass index, all metabolically unhealthy groups displayed increased risks. CONCLUSIONS AND RELEVANCE: This newly proposed definition of MH may identify a subgroup of people with obesity without increased risk of mortality and stratify risks in people who are overweight or normal weight.